Membaca Nilai Sufistik dalam Kumpulan Puisi Mencari Sebuah Masjid Editor Husnu Abadi dan Nopri Ahadi - Shomary, Sudirman (GERAM: Gerakan Aktif Menulis, 2022)
The anthology of poetry Looking for a Mosque, editors Husnu Abadi and Nopri Ahadi contains 24 titles of poems by well-known Indonesian authors. This work was published as material for a poetry reading competition in commemoration of Islamic Holidays. That is why this anthology of poetry contains many religious themes and Sufistic values. The problem studied is how are the Sufistic values ​​contained in the anthology of the poem Looking for a Mosque? This study uses descriptive analysis and content analysis methods. The results of the study found Sufistic values ​​related to the rituals or worship of Ramadan, Eid al-Fitr, mosques, and the Hajj. Poems about Ramadan worship were embroidered by poets in the poem Malam Qadar by Idrus Tintin, Night of a Thousand Months by Husnu Abadi. Furthermore, Sutardji Calzoum Bachri's Eid-ul-Fitr poem clearly explains about the worship of Ramadan and its night worship and almsgiving can lead one to become His pious servant. The Sufistic value of worship is to draw the servant closer to God, namely Allah SWT (hal taqarrub ilallah). In addition, there are also mystical values ​​related to repenting to God and the low position of servants in front of God Almighty. This anthology of poetry contains maqam wara and maqam zuhud which means the servant's closeness to His Creator because of his special worship and his simple and sincere way of life.